Modelling in Medicine and Biology VI 2005
DOI: 10.2495/bio050061
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of subject specific ICP dynamic models using prospective clinical data

Abstract: We used a prospective clinical trial to generate physiologic data to create subject-specific in silico (computer simulation) models of intracranial pressure dynamics in children with severe traumatic brain injury. The trial included a physiologic challenge protocol with changes in head-of-bed elevation and minute ventilation, applied over multiple iterations to three subjects. Physiologic signals (electrocardiogram, respiration, arterial blood pressure, intracranial pressure [ICP], oxygen saturation) were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Consistent with prior investigators (15,17), autoregulation is modeled as a feedback loop . We have previously shown that the behavior of our model was qualitatively correct (11,12), and we were able to manually calibrate the model so that it replicated retrospective clinical data from two prior subject-specific cases (13). Preliminary parameter estimation results were reported in (12).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Consistent with prior investigators (15,17), autoregulation is modeled as a feedback loop . We have previously shown that the behavior of our model was qualitatively correct (11,12), and we were able to manually calibrate the model so that it replicated retrospective clinical data from two prior subject-specific cases (13). Preliminary parameter estimation results were reported in (12).…”
Section: Discussionmentioning
confidence: 91%
“…Some parameter estimates derived from the laboratory data and/or clinical data have been reported, but much of the necessary data remains difficult to obtain. Models have been calibrated to fit data recorded for specific patients (7,8,(11)(12)(13)(17)(18)(19)(20)(21) and excellent results have been reported in some cases (8,21). However, to our knowledge actual prediction of patient-specific ICP response to therapies or other interventions has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations